ANALISIS IMPLEMENTASI PENILAIAN AUTENTIK PADA MATA PELAJARAN EKONOMI KELAS X2s DI SMA PERTIWI AMBON - Amjad Salong; Novita E Latupeirissa (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This study aims to determine the Implementation of Authenti Assessment in Economic Subjects of Class X2 in SMA Pertiwi Ambon T.A 2020/2021. In this study, the type of research used is the type of descriptive research is research conducted to determine the value of independent variables, either one variable or more without making comparisons or connecting with other variables. Data collection techniques used in this study were questionnaires and documentation, questionnaires were used to obtain data on the implementation of authentic assessment conducted by economics teachers in learning, while documentation was used to collect data in the form of archives or documents related to this study.The results showed that of the six indicators presented in this research variable, the average was at 50% and included in the qualifications was quite good. So that the implementation of authentic assessment implemented by economics teachers is quite good.